Ectopic expression of R2R3-MYB transcription factors to control suberin biosynthesis - Berning, Nick, author; Medford, June, advisor; Peebles, Christie, committee member; Sloan, Dan, committee member (Colorado State University. Libraries, 2022)
Minimizing the deleterious effects of abiotic stresses on cultivated plants is critical to maximizing crop yield. Suberin is a glycerol based polyester found in the endodermis, seed coat, cork cells, and areas of wounding in the epidermis. Recently, suberin biosynthesis has been shown to be at least partially regulated by a set of R2R3-MYB transcription factors. The ability to control suberin biosynthesis in specific plant tissues could be a valuable biotechnological tool in designing plants which can withstand higher degrees of abiotic stress. In this thesis, I detail a genetic screen of four different R2R3-MYB transcription factor's ability to induce ectopic suberin formation in the root epidermis of Arabidopsis thaliana. Subsequently, I characterize the transcription factor with the greatest ability to induce ectopic suberin biosynthesis, MYB92. MYB92, when expressed in the root epidermis, consistently forms a suberin barrier within that tissue. Plants expressing MYB92 in the root epidermis may be stunted and chlorotic under typical growth conditions, however, they outperform wild-type Col-0 plants under salt stress. More characterization of ectopic, suberin barrier's ability to confer salt tolerance could be performed in order to understand how epidermal suberin might perform in crop plants.